Complications After Vesicovaginal Fistula Repair Based on Surgeon Specialty in the United States: Analysis of a National Database. Issue 3 (March 2022) - Romanova, Anna; Sifri, Yara; Gaigbe-Togbe, Bertille; Menhaji, Kimia; Tran, Ann; Hardart, Anne; Dabney, Lisa
Abstract : Objectives: This study aimed to compare the rates of major and minor complications for vesicovaginal fistula (VVF) repair based on surgeon specialty and to identify risk factors for adverse outcomes. Methods: This was a retrospective cohort analysis of the American College of Surgeons National Surgical Quality Improvement Program between the years 2014 and 2019. Cases were identified using Current Procedural Terminology codes for VVF repair. Minor and major complication rates for VVF repair were compared between 2 cohorts defined by surgeon specialty: gynecology versus urology. Additional outcomes included readmissions and reoperations. Multivariable logistic regression analysis was performed to investigate risk factors for complications. Results: A total of 319 VVF repairs were included in the analysis, of which 115 (36.1%) were performed by gynecologists and 204 (63.9%) by urologists. There were no significant differences in the demographic or medical characteristics between the gynecology and urology cohorts except for race. Gynecologists performed more concomitant hysterectomies (10.4% vs 1.0%, P < 0.001) and apical suspension procedures (6.1% vs 0%, P < 0.001). There were no differences in minor (7.8% vs 6.4%, P = 0.623) or major (2.6% vs 3.4%, P = 1.000) complications between the cohorts. The overall readmission rate was 4.7%, and the reoperation rate was 2.2% with no differences between specialties. On multivariable logistic regression analysis, body mass index and concurrent hysterectomy were risk factors for major or minor complications with no increased risk associated with surgeon specialty or route of surgery. Conclusions: Complication rates did not differ for VVF repairs performed by gynecologists compared with urologists. Readmission and reoperation rates were low for both groups.